Enzyme-Based Antiviral Potential of Cinnamomum verum J. Presl. Essential Oil and Its Major Component (E)-Cinnamaldehyde - Karadag, Asra; Biltekin, Sevde Nur; Ghani, Usman; Demirci, Betul; Demirci, Fatih (Amer Chemical Soc, 2024)
In the present study, Cinnamomum verum J. Presl. bark essential oil and its main component cinnamaldehyde was evaluated in vitro for neuraminidase (NA), transmembrane serine protease (TMPRSS2), and angiotensin converting enzyme 2 (ACE2) inhibitory activities. The chemical composition of C. verum essential oil was confirmed by both gas chromatography-mass spectrometry (GC/MS), and gas chromatography-flame ionization detection (GC-FID), where 75.9% (E)-cinnamaldehyde was the major component. The ACE2, NA, and TMPRSS2 enzyme inhibitions of C. verum bark essential oil at 20 mu g/mL concentration, and (E)-cinnamaldehyde (5 mu g/mL) were calculated and compared in the range of 54.2-89.9%. Molecular docking results supported that (E)-cinnam-aldehyde was specific to ACE2 with 89.9% inhibition. Our findings suggest further in vivo studies to confirm the effective and safe use of the essential oil as well as the (E)-cinnamaldehyde.
Keywords: Ace2; Binding